TNF-α–mediated bronchial barrier disruption and regulation by src-family kinase activation - Hardyman, Michelle A.; Wilkinson, Emily; Martin, Emma; Jayasekera, Nivenka P.; Blume, Cornelia; Swindle, Emily J.; Gozzard, Neil; Holgate, Stephen T.; Howarth, Peter H.; Davies, Donna E.; Collins, Jane E. (Journal of allergy and clinical immunology, 2013)
Because TNF-α is increased in severe asthma, we hypothesized that TNF-α contributes to barrier dysfunction and cell activation in bronchial epithelial cells. We further hypothesized that src-family kinase inhibition would improve barrier function in healthy cells in the presence of TNF-α and directly in cultures of severe asthmatic cells where the barrier is disrupted. We assessed the effect of TNF-α, with or without src-family kinase inhibitor SU6656, on barrier properties and cytokine release in differentiated human bronchial epithelial cultures. Further, we tested the effect of SU6656 on differentiated primary cultures from severe asthma. Barrier properties of differentiated human bronchial epithelial air-liquid interface cultures from healthy subjects and subjects with severe asthma were assessed with transepithelial electrical resistance and fluorescent dextran passage. Proteins were detected by immunostaining or Western blot analysis and cytokines by immunoassay. Mechanisms were investigated with src kinase and other inhibitors. TNF-α lowered transepithelial electrical resistance and increased fluorescent dextran permeability, caused loss of occludin and claudins from tight junctions with redistribution of p120 catenin and E-cadherin from adherens junctions, and also increased endogenous TNF-α, IL-6, IL-1β, IL-8, thymic stromal lymphoprotein, and pro–matrix metalloprotease 9 release. SU6656 reduced TNF-α–mediated paracellular permeability changes, restored occludin, p120, and E-cadherin and lowered autocrine TNF-α release. Importantly, SU6656 improved the barrier properties of severe asthmatic air-liquid interface cultures. Redistribution of E-cadherin and p120 was observed in bronchial biopsies from severe asthmatic airways. Inhibiting TNF-α or src kinases may be a therapeutic option to normalize barrier integrity and cytokine release in airway diseases associated with barrier dysfunction.